The effect of real-time visual feedback and verbal encouragement on repetition velocity of squat, bench press and deadlift exercises in competitive powerlifters - Concon, V.; Kobal, R.; Carvalho, L.; Crivoi do Carmo, E.; Coimbra, D.; Barroso, R. (International Journal of Sports Science & Coaching, 2025)
This study aimed to compare the effects of real-time visual feedback, verbal encouragement, and no-feedback control condition on repetition velocity. Twelve highly-trained powerlifters (10 men and 2 women) participated in a crossover-designed experiment, performing the same training session under three conditions: real-time visual feedback (VF), verbal encouragement (VE), and control. The training session involved three sets of four repetitions in the squat, bench press, and deadlift exercises, with a workload set at 70% of one-repetition maximum (1RM). Repetition velocity was measured using a linear encoder. In the VF condition, participants observed their velocity on a mobile screen after each repetition. In the VE condition, participants received verbal encouragement without access to velocity information on the screen. The Control condition provided no feedback. A mixed model analysis was used to compare velocity across repetitions, sets, and conditions. Results revealed differences between the control condition and both VE and VF in the squat and bench press exercises (p < 0.05). Only in the VF condition, velocity was higher than control in the deadlift exercise (p < 0.05). Coaches and practitioners are encouraged to use real-time visual feedback and/or verbal encouragement during training to enhance repetition velocity. Incorporating these feedback strategies during strength training of highly-trained powerlifters can improve velocity performance.